2017
DOI: 10.1627/jpi.60.19
|View full text |Cite
|
Sign up to set email alerts
|

High Strength Polyacrylamide/nmSiO<sub>2</sub> Composite Hydrogel for Well Killing

Abstract: Killing pills of high strength composite hydrogel were prepared by polyacrylamide, chromium acetate crosslinker and silica nanoparticles reinforcer. The killing performance of composite hydrogel depended on its viscoelasticity and compression strength, which were both influenced by polymer content, ratio of polymer to chromium acetate and nano silica content. In this work, the effect of these altering factors on strength of composite hydrogel were evaluated, results showed that elastic moduli (G′), viscous mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Under the same strain of 45%, the composite gel with 8% nanosilica possessed the stress of 44.6 KPa, which is nearly 10 times higher than the general gel without nanosilica with the stress less than 5 KPa, indicating its excellent mechanical and elasticity strength. The stress-strain performance of this new developed composite gel is better than the nanosilica-based PAM crosslinking chromium acetate nanocomposite gel reported by Sun et al 31,32 After the compress load was released, as it is shown in Figure 4, the general gel (without adding nanosilica) cracked, and there are obvious wide fractures on the bottom, whereas the composite gel with 8% nanosilica is still an undamaged whole with no fractures but a very little shape change. That could be explained as there are more empty space in the general gel network structure, when then general gel was compressed, it is brittle and easy to crack.…”
Section: Stress-strain Performancementioning
confidence: 68%
See 2 more Smart Citations
“…Under the same strain of 45%, the composite gel with 8% nanosilica possessed the stress of 44.6 KPa, which is nearly 10 times higher than the general gel without nanosilica with the stress less than 5 KPa, indicating its excellent mechanical and elasticity strength. The stress-strain performance of this new developed composite gel is better than the nanosilica-based PAM crosslinking chromium acetate nanocomposite gel reported by Sun et al 31,32 After the compress load was released, as it is shown in Figure 4, the general gel (without adding nanosilica) cracked, and there are obvious wide fractures on the bottom, whereas the composite gel with 8% nanosilica is still an undamaged whole with no fractures but a very little shape change. That could be explained as there are more empty space in the general gel network structure, when then general gel was compressed, it is brittle and easy to crack.…”
Section: Stress-strain Performancementioning
confidence: 68%
“…Under the same strain of 45%, the composite gel with 8% nanosilica possessed the stress of 44.6 KPa, which is nearly 10 times higher than the general gel without nanosilica with the stress less than 5 KPa, indicating its excellent mechanical and elasticity strength. The stress–strain performance of this new developed composite gel is better than the nanosilica‐based PAM crosslinking chromium acetate nanocomposite gel reported by Sun et al…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plugging layer is formed by a curing reaction or volume expansion at the loss-circulation zone, which has the advantages of a low density of plugging slurry, adjustable gelling time and strong ability of plugging slurry to control filtration loss [3][4][5][6][7][8]. The commonly used polymer gel plugging system usually has strong viscoelasticity and deformability [9], and it has been successfully applied in some areas, such as the fractured vicious loss ground layer in northeast Sichuan and other places. In 2018, Bai Yang et al [10] put forward gel lost circulation slurry and lost circulation slurry for drilling.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the slurry can quickly form a structure at the fracture of the loss-circulation formation. In 2020, Zhang Hongxu et al [11] proposed a semi-interpenetrating network gel The commonly used polymer gel plugging system usually has strong viscoelasticity and deformability [9], and it has been successfully applied in some areas, such as the fractured vicious loss ground layer in northeast Sichuan and other places. In 2018, Bai Yang et al [10] put forward gel lost circulation slurry and lost circulation slurry for drilling.…”
Section: Introductionmentioning
confidence: 99%